Identification of a clinicopathologic prognostic index for newly diagnosed large B cell lymphoma patients treated with R-CHOP - Vincent Ni; Sunita D. Nasta; Stefan K. Barta; Stephen J. Schuster; Elise A. Chong; Jakub Svoboda; Jennifer J.D. Morrissette; Ashley Barlev; Adam Bagg; Salvatore F. Priore; Daniel J. Landsburg (Haematologica, 2024)
Not available.